MENATA IUS CONSTITUTUM MENUJU SATU SISTEM HUKUM NASIONAL - Rachmat Trijono (VERITAS, 2020)
Criticism of the ius constitutum of Indonesia which is still not organized according to the appropriate grading and grundnorm has resulted in a reconstruction of the arrangement of the ius constitutum. The purpose of this paper is to reconstruct the arrangement of the constitutum ius which is spread in various scientific papers by the author. The method used is a qualitative method with a descriptive approach. The conclusion was that efforts had been made to rearrange the ius constitutum, however, if it was not carried out in a focused and thorough manner, there would not be a single national legal system that was unique and suited to the Indonesian situation. The necessity of realizing a national legal system is not just a dream.